Transformation Of The Geographic Information System For The Distribution And Monitoring Of Stunting Children Using Epicollect5 At Nuangan Community Health Center - Harikedua, Vera T.; Pascoal, Meildy Esthevanus; Sambuaga, Joy V.L (Dian Nuswantoro Semarang, 2025)
In the era of rapid development of digital technology, digitalisation has become a key driver of transformation in various sectors of life. In particular, in the context of health, digitalisation offers great potential to improve access, efficiency and quality of health services. On the other hand, health literacy is a critical aspect to ensure people can optimise the benefits of technological developments. This research aims to build a Geographic Information System for mapping the distribution of stunting and improving the ability of cadres in handling and preventing stunting based on digital android. The research method used involves field surveys, health data collection, and the use of GIS technology to analyse the spatial distribution and risk factors for stunting. The results with this system are able to provide a geographic information system for the distribution in each sub-district and village by providing prevalence information and in handling it provides a forecasting feature for predicting the distribution of stunting in the next period, in order to anticipate the increase in stunting rates in Nuangan District. Conclusion: The process of reading data visualisation on the map of spatial analysis results can help cadres and health workers in understanding stunting problems in the community.